Study Orchestrations in Distance Learning: Identifying Dissonance and its Implications for Distance Educators - Anderson, Bill; Lee, Scott W. F.; Simpson, Mary G.; Stein, Sarah J. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The exploration of study orchestrations emphasises students’ active participation in learning, describing the ways in which they marshal the resources available to them in response to their learning environment. This study reports the identification of study orchestrations in a group of distance students and identifies the existence of dissonant study orchestrations, which previous research has linked with poor achievement, in approximately one-fifth of the group. Data came from responses by 176 students to the ASSIST questionnaire. The data was subject to factor analysis to ensure commensurability with previous studies, and then cluster analysis was used to identify groups with similar study orchestrations. Four clusters were identified. One of these was clearly dissonant, pointing toward problematic links between learning environments and student approaches to study. The implications of dissonant study orchestrations are explored and further research is suggested, along with implications for the practice of distance educators.